Pengaruh Kompensasi, Disiplin Kerja, dan Motivasi Terhadap Kinerja Karyawan PT. Lontar Papyrus Pulp and Paper Industry - Rozi, A; Marnas, Marnas; Evrina, Evrina (ILTIZAM Journal of Shariah Economics Research, 2025)
This study aims to examine the effect of compensation, work discipline, and motivation on the performance of production employees at PT. Lontar Papyrus Pulp and Paper Industry. A quantitative research approach was employed, with data collected through interviews and the distribution of questionnaires. The sampling technique applied was purposive sampling, involving a total of 50 production employees as respondents. Data analysis was conducted using SmartPLS 4.0. The findings reveal that compensation has a statistically significant impact on employee performance, as indicated by a t-statistic value exceeding the critical t-table threshold (3.923 > 1.677) and a p-value below the 5% significance level (0.000 < 0.05). Conversely, work discipline does not exhibit a significant effect on employee performance, with a t-statistic value below the threshold (0.614 < 1.677) and a p-value above 5% (0.270 > 0.05). Additionally, motivation is found to significantly influence employee performance, supported by a t-statistic value greater than the t-table (2.854 > 1.677) and a p-value less than 5% (0.002 < 0.05).